Systems, software and services process improvement : 23rd European Conference, EuroSPI 2016, Graz, Austria, September 14-16, 2016, proceedings /: 23rd European Conference, EuroSPI 2016, Graz, Austria, September 14-16, 2016, proceedings. (2016) - Unknown
No abstract available